If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 47 + -3x = 6x + 21 Reorder the terms: 47 + -3x = 21 + 6x Solving 47 + -3x = 21 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 47 + -3x + -6x = 21 + 6x + -6x Combine like terms: -3x + -6x = -9x 47 + -9x = 21 + 6x + -6x Combine like terms: 6x + -6x = 0 47 + -9x = 21 + 0 47 + -9x = 21 Add '-47' to each side of the equation. 47 + -47 + -9x = 21 + -47 Combine like terms: 47 + -47 = 0 0 + -9x = 21 + -47 -9x = 21 + -47 Combine like terms: 21 + -47 = -26 -9x = -26 Divide each side by '-9'. x = 2.888888889 Simplifying x = 2.888888889
| 5x+2=-x | | 7(3x+4)-1=-78 | | 7x+42=x+12 | | 4x^2=9+41 | | 7e^4x-5=11 | | 7x+3x=44 | | -x+x-2=2 | | 10x+45=x+81 | | 7x+3x=72 | | 12-(n-3)= | | 7=2x+11 | | R+4=20 | | z+4.9=8.8 | | 7x+60=x-6 | | 45=-5(k+4) | | 2/5x-=1/5x-12 | | 2sin^2-3cos+1=0 | | 11a^2+2a-17=0 | | 5a+6a=-6+8a | | 360=(x+40)+(4x+70)+(2x+110) | | x+47=54 | | 4x^2-2-8w=-6x | | -14x+1=21 | | 360=(x+50)+(2x+80)+(4x+20) | | x^4-5x^3-2x^2-3x-9= | | 5y-(3y+8)=3-(7y-9) | | 5(x-1)=3(2-x)-5 | | x+52=61 | | 11v-2v=54 | | x+78=86 | | 90x^2-63xy+18x=0 | | 7=m/125 |